Back Cover: Selective Capture of Carbon Dioxide under Humid Conditions by Hydrophobic Chabazite‐Type Zeolitic Imidazolate Frameworks (Angew. Chem. Int. Ed. 40/2014). Issue 40 (22nd July 2014) - Nguyen, Nhung T. T.; Furukawa, Hiroyasu; Gándara, Felipe; Nguyen, Hoang T.; Cordova, Kyle E.; Yaghi, Omar M.
<x xml:space="preserve">Abstract</x> Selective capture of CO2 in the presence of N2 and H2O is possible with hydrophobic zeolitic imidazolate frameworks (ZIFs) with the important chabazite topology. These materials, described by O. M. Yaghi and co‐workers in their Communication on page 10645 ff., are shown to perform three consecutive cycles without loss in performance. Remarkably, between each cycle, the ZIFs were fully regenerated at ambient temperature by using N2 flow.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>